Effects of pitch size on soccer players` physiological, physical, technical, and tactical responses during small-sided games: a meta-analytical comparison - Clemente, F. M.; Moreira Praça, G.; Aquino, R.; Castillo, D.; Raya-González, J.; Rico-González, M.; Afonso, J.; Sarmento, H.; Silva, A. F.; Silva, R.; Ramirez-Campillo, R. (Biology of Sport, 2023)
One of the most often-used task constraints in designing small-sided games (SSGs) is the manipulation of pitch size to promote increases or decreases in the relative area per player. Such adjustments cause hanges in the acute responses during SSGs. This systematic review with meta-analysis aimed to compare the effects of smaller vs. larger pitch sizes on soccer players` physiological, physical, technical, and tactical responses during SSGs. Comparisons between smaller and larger pitches were not considered based on a specific size, but also between using at least two dimensions in the same comparative study, aiming to understand differences between using smaller and larger (independently of the specific dimensions). The data sources utilized were PubMed, PsycINFO, Scielo, Scopus, SPORTDiscus, and Web of Science. The database search initially yielded 249 titles. From those, 41 articles were eligible for the systematic review and meta-analysis. Results revealed that, compared to smaller pitches, SSGs played on larger pitches induced greater values for heart rate (p < 0.001; ES = 0.50), rate of perceived exertion (p < 0.001; ES = 0.70), total distance (p < 0.001; ES = 1.95), high-speed running (p < 0.001; ES = 1.20), stretch index (p < 0.001; ES = 1.02) and surface area (p < 0.001; ES = 1.54). No significant differences were found between pitch size regarding the numbers of accelerations (p = 0.232; ES = 0.45), decelerations (p = 0.111; ES = 0.85), passes (p = 0.897; ES = 0.02), dribbles (p = 0.823; ES = -0.05), or positional centroid (p = 0.053; ES = 0.56). Larger pitch sizes can be implemented as a meaningful task constraint to increase the internal and external load experienced by soccer players during SSGs, as well as to increase the dispersion of players while acting together. These results were found independent of format and age group.